Treatment with recombinant human tumor necrosis factor-alpha protects rats against the lethality, hypotension, and hypothermia of gram-negative sepsis. - H R Alexander; B C Sheppard; J C Jensen; H N Langstein; C M Buresh; D Venzon; E C Walker; D L Fraker; M C Stovroff; J A Norton (The Journal of Clinical Investigation, 1991)
Tumor necrosis factor (TNF) is a peptide secreted by macrophages in response to endotoxin that can produce many of the changes seen in septic shock. After cecal ligation and puncture (CLP) rats gradually develop tachycardia, hypotension, tachypnea, and hypothermia. At 5 h post-CLP, rats have a peak in serum levels of endotoxin and 60% of rats have blood cultures that grow Gram-negative rods (Escherichia coli and Klebsiella pneumonia). At 20 h post-CLP all rats develop positive blood cultures. Serum levels of TNF are not reproducibly measurable in rats following CLP. Rats undergoing CLP have a 50-80% mortality with deaths usually occurring 24-72 h postinjury. Repetitive (twice daily x 6 d) i.p. injection of sublethal doses of recombinant human TNF-alpha (100 micrograms/kg) to rats undergoing CLP 1 d after the treatment period resulted in a significant reduction in mortality compared to control rats previously unexposed to rTNF (P less than 0.03). Animals treated with rTNF had no hypotension or hypothermia after CLP and regained normal food intake faster than control rats. 12 h after CLP the gene expression for manganous superoxide dismutase (MnSOD), an inducible mitochondrial metalloenzyme responsible for cellular resistance to injury from toxic reactive oxygen species, was higher in livers of rats treated with rTNF suggesting that the TNF treatment augmented expression of this protective enzyme. Unlike MnSOD, expression of the gene for copper-zinc SOD was not affected by CLP or rTNF treatment. The results suggest that prior treatment with recombinant TNF can ameliorate the lethality, hypotension, hypothermia, and anorexia of Gram-negative sepsis in rats and that the mechanism may be related to enhanced hepatic expression of the gene for MnSOD. Repeated administration of recombinant TNF may be a strategy to minimize mortality and morbidity of Gram-negative sepsis. Images